2020
DOI: 10.1590/1678-4685gmb-2019-0138
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication stress: oncogenes in the spotlight

Abstract: Precise replication of genetic material is essential to maintain genome stability. DNA replication is a tightly regulated process that ensues faithful copies of DNA molecules to daughter cells during each cell cycle. Perturbation of DNA replication may compromise the transmission of genetic information, leading to DNA damage, mutations, and chromosomal rearrangements. DNA replication stress, also referred to as DNA replicative stress, is defined as the slowing or stalling of replication fork progression during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 145 publications
(214 reference statements)
0
16
0
Order By: Relevance
“…MDM2 transgenic mice also showed increased chromosome breaks, chromosome fusions, aneuploidy, and polyploidy (Lushnikova et al, 2011). It has also been shown that p53 disruption by MDM2 overexpression activates the intra S-phase checkpoint to inhibit DNA replication origin firing, causing replication fork instability (Frum et al, 2014;Primo and Teixeira, 2019).…”
Section: Mdm2 Affects Genomic Instability In P53-dependent Mannermentioning
confidence: 99%
“…MDM2 transgenic mice also showed increased chromosome breaks, chromosome fusions, aneuploidy, and polyploidy (Lushnikova et al, 2011). It has also been shown that p53 disruption by MDM2 overexpression activates the intra S-phase checkpoint to inhibit DNA replication origin firing, causing replication fork instability (Frum et al, 2014;Primo and Teixeira, 2019).…”
Section: Mdm2 Affects Genomic Instability In P53-dependent Mannermentioning
confidence: 99%
“…Oncogene activation, another hallmark of cancer, may interfere with normal cell proliferation and DNA replication. In fact, certain oncogenes are able to induce replication stress and promote genomic instability in human carcinogenesis ( Primo and Teixeira, 2019 ). One such example is oncogenic Cyclin E/CDK2 complex.…”
Section: Cyclin E/cdk2-induced Replication Stress Causes Genomic Instability In Human Cancersmentioning
confidence: 99%
“…These mutations include activating mutations in BRAF, RAS (KRAS and HRAS), and PTPN11 (78), which encodes the tyrosine phosphatase SHP-2, and inactivating mutations in the NF1 tumor suppressor gene (91), a negative regulator of RAS (92). Activation of the RAS signaling pathway leads to replication stress by driving DNA replication, by a similar mechanism to MYCN overexpression (93,94). (17).…”
Section: Alk and Map Kinase Pathwaysmentioning
confidence: 99%